EFFECT OF HEALTH PROMOTION PROGRAM WITH HEALTH BEHAVIOR AMONG VILLAGE HEALTH VOLUNTEERS RISK ON HYPERTENSION NONG PHAI LOM SUB-DISTRICT, MUEANG DISTRICT, NAKHON RATCHASIMA PROVINCE - แดงงาม , สิริพร; เพชรมณี, สาโรจน์; ปัญญาใสโสภณ, ธณกร (Primary Health Care Journal (Northeastern Edition), 2024)
This quasi-experimental study aimed at the effect of health promotion program with health behavior among village health volunteers’ risk on hypertension Nong Phai Lom Sub-district, Mueang District, Nakhon Ratchasima Province. The samples were divided into two groups. The experimental group consisted of 35 participate groups that received Pender Health Promotion Application Program with 3E 2S, and the control group consisted of 35 non received regular health promotion programs by Simple random sampling. The instrument was a health promotion program, questionnaire and blood pressure recording form. Frequencies, percentage, mean, standard deviation, paired samples t-test and independent samples t-test were applied for data analysis. The results of this study were as follows: After receiving the health promotion program the village health volunteers risk on hypertension Nong Phai Lom Sub-district, Mueang District, Nakhon Ratchasima Province, The experimental group had health behavior : food, stress, exercise, reducing each quitting smoking and alcohol had significantly better health promotion program than before receiving the health promotion program and control group at .01 level and the experimental group had lower blood pressure levels than the control group at .05 levels. (Mean=121.13, SD=5.59/77.66 SD=4.04 mmHg.)